A new function for the serine protease HtrA2 in controlling radiation‐induced senescence in cancer cells. Issue 6 (16th February 2022) - Hammer, Liat; Levin‐Salomon, Vered; Yaeli‐Slonim, Naama; Weiss, Moria; Dekel‐Bird, Naama P.; Olender, Tsviya; Porat, Ziv; Winograd‐Katz, Sabina; Savidor, Alon; Levin, Yishai; Bialik, Shani; Geiger, Benjamin; et al.
Abstract : Radiation therapy can induce cellular senescence in cancer cells, leading to short‐term tumor growth arrest but increased long‐term recurrence. To better understand the molecular mechanisms involved, we developed a model of radiation‐induced senescence in cultured cancer cells. The irradiated cells exhibited a typical senescent phenotype, including upregulation of p53 and its main target, p21, followed by a sustained reduction in cellular proliferation, changes in cell size and cytoskeleton organization, and senescence‐associated beta‐galactosidase activity. Mass spectrometry‐based proteomic profiling of the senescent cells indicated downregulation of proteins involved in cell cycle progression and DNA repair, and upregulation of proteins associated with malignancy. A functional siRNA screen using a cell death‐related library identified mitochondrial serine protease HtrA2 as being necessary for sustained growth arrest of the senescent cells. In search of direct HtrA2 substrates following radiation, we determined that HtrA2 cleaves the intermediate filament protein vimentin, affecting its cytoplasmic organization. Ectopic expression of active cytosolic HtrA2 resulted in similar changes to vimentin filament assembly. Thus, HtrA2 is involved in the cytoskeletal reorganization that accompanies radiation‐induced senescence and the continuous maintenance of proliferation arrest. Abstract : Htra2, a mitochondrial serine protease that is a known regulator of apoptosis, was identified through an siRNA screen as a positive mediator of radiation‐induced senescence in cancer cells. Following irradiation, Htra2 enables continuous maintenance of proliferation arrest and cleaves the intermediate filament protein vimentin, leading to filament disassembly and cytoskeletal reorganization.